PENERAPAN FLIPPED CLASSROOM DALAM KONTEKS EDUCATION FOR SUSTAINABLE DEVELOPMENT UNTUK MENINGKATKAN KEMAMPUAN KOGNITIF DAN MEMBANGUN SUSTAINABILITY AWARENESS SISWA SMP PADA MATERI ENERGI - Gabriela clarisa, - (2020)
This research is motivated by the unpreparedness of students when learning in class because of most students keep their handbooks at school. One of the ways to solve these probllems is by using the flipped classroom model. Flipped Classroom is a 21st century teaching method that facilitates students to autonomously learn outside the classroom, followed by discussions or active learning in the classroom. Education for Sustainable Development (ESD) refers to contexts or issues that could be discussed in the preferred teaching method in relation to ESD which aims to develop students' Sustainability Awareness. This research was conducted in the form of one group pretest-posttest design, involving 29 students in a State-Owned Secondary School in Bandung. Several instruments were used in this research including a cognitive scale in the form of multiple choice test, Sustainability Awareness questionnaires and observation sheets to collect data related to the Flipped Classroom implementation within the context of ESD. The results of this research indicated that the implementation of Flipped Classroom within the context of ESD successfully improved students' cognitive skill and developed students' Sustainability Awareness.